2022
DOI: 10.3389/fpain.2022.897725
|View full text |Cite
|
Sign up to set email alerts
|

Brief Pain Inventory Pain Interference Subscale: Assessing Interference With Daily Living Activities in Older Adults With Multisite Musculoskeletal Pain

Abstract: ObjectivesThis study aims to determine domains of pain interference in daily routines assessed using the Brief Pain Inventory, in relation to multisite musculoskeletal pain among older adults living in the community.DesignThe MOBILIZE Boston Study is a population-based study of 749 adults aged 70 and older.MeasurementsChronic musculoskeletal pain was assessed using a joint pain questionnaire and grouped as: no pain, single-site and multisite pain. The Brief Pain Inventory pain interference (PI) sub-scale asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…In all seven domains of pain impairment, there was a statistically significant difference compared to the tested groups. The results of our study are not consistent with the results of the MOBILIZE study, conducted in Boston on 749 people over 70 years of age, in which the presence and intensity of pain affected two domains in particular -"general activities" and "walking" (14). Iliffe et al indicated in their study that chronic pain has a variety of effects on daily life and activities, including functional limitations, fatigue, sleep problems, and depressive mood, which significantly affect quality of life (15).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In all seven domains of pain impairment, there was a statistically significant difference compared to the tested groups. The results of our study are not consistent with the results of the MOBILIZE study, conducted in Boston on 749 people over 70 years of age, in which the presence and intensity of pain affected two domains in particular -"general activities" and "walking" (14). Iliffe et al indicated in their study that chronic pain has a variety of effects on daily life and activities, including functional limitations, fatigue, sleep problems, and depressive mood, which significantly affect quality of life (15).…”
Section: Discussioncontrasting
confidence: 99%
“…The questions are worded to capture the variability of pain over time, including worst pain, least pain, average pain, and current pain. The questionnaire also includes questions about the number and type of current treatments and their perceived effectiveness, the degree to which pain affects general activity, mood, ability to walk, normal work, relationships with others, sleep, and enjoyment of life, on a 1-10 point scale (14). Because the questionnaire is licensed material, written consent was required for its use in the study.…”
Section: Methodsmentioning
confidence: 99%
“…A cut‐off was used to differentiate between high (≥7) and low (<7) interference levels 24 . Participants' musculoskeletal pain distribution was categorized into seven sites and the number of sites was grouped as no pain, single site pain, or multisite pain (≥2 sites) 25 …”
Section: Resultsmentioning
confidence: 99%
“… 24 Participants' musculoskeletal pain distribution was categorized into seven sites and the number of sites was grouped as no pain, single site pain, or multisite pain (≥2 sites). 25 c For EQ‐ED‐EL, an index was derived using the value set for Ireland. 31 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation